HUBUNGAN ANTARA BUDAYA ORGANISASI DENGAN DISIPLIN KERJA GURU DI SMP NEGERI 5 PERCUT SEI TUAN - Asyari, Muhammad Nazhif; Siregar, Zainal Abidin; Santosa, Fitrah (Jurnal Manajemen Pendidikan, 2017)
Discipline must be established within a school organization. Without the support of good teacher discipline, it is difficult for schools to realize their goals. So, discipline is the key to a school's success in achieving its goals. Lack of teacher discipline in SMP Negeri 5 percy sir, because there are still many teachers who do not understand the rules that exist in school, as there are many teachers who arrived late, and late into the classroom, there are still many teachers who leave the time the subject takes place. This research uses quantitative approach with correlation. Correlational research is intended to determine whether there is a relationship between two variables. Population amount in this study as many as 55 respondents. While the sample amounted to 48 respondents. The result of this research are: 1) the calculation result of regression of Y over X shows F arithmetic regression obtained 10,740 while price Ftabel with dk pembilang 1 and dk denominator 46 at significance level α = 0,05 is 4,042. Apparently the price of F arithmetic (10,740) is greater than the price of F table (4,042) it can be concluded that the regression coefficient of Y over X means at the significance level α = 0.05. This means that the regression direction coefficient Ŷ = 44,095 + 0,330 X so it can be concluded there is relationship between organizational culture with teacher work discipline.